Middle leadership in international schools: evidence from Malaysia - Javadi, Vahid; Bush, Tony; Ng, Ashley (Taylor & Francis, 2017)
This paper examines middle leadership of the heads of English, maths and science departments in four international secondary schools in Malaysia. It focuses on their roles, responsibilities, role relationships, instructional engagement and leadership involvement within the theoretical framework of instructional, distributed and teacher leadership. The study is a qualitative multi-method case study, involving observation, documentary analysis, and semi-structured interviews with 12 heads of department, 36 teachers, and four principals. With respect to the middle leaders’ roles and responsibilities, the findings illustrate cross-school and in-school differential developments, with contextual factors contributing to uneasy role relationships. The results also show that, while broad-based leadership opportunities are limited for the middle leaders and teachers, the most powerful and common feature of all these international schools is the centrality of teaching and learning.